(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to study the impact of the financing activities on the profitability of Islamic banks operating in Syria during the period 2011-2022. The study used the return on equity and the return on equity of unrestricted investment account holders as dependent variables, while total deposits, receivables and balances of financing activities are included as independent variables, and Inflation as a controlling variable; This is due to the fact that the study period was characterized by high rates of inflation. The study used cross-sectional time series (Panel data), where a set of statistical tests were conducted to choose the appropriate model, the unit root tests indicated that the variables differ in the degree of their stability, so the dynamic models were adopted, and ARDL methodology was used. The study found that there is a Positive, significant effect of financial receivables and activities on the return on equity and an insignificant Positive effect on the return on the unrestricted investment account holders, while it found a negative insignificant effect of deposits on the return on equity and the return on the unrestricted investment account holders. In light of the results, the study presented a set of recommendations; Such as increasing investment activities as it is an important source of profits, and managing deposits more efficiently in order for the bank and investment account holders to achieve more profits.